Ultrasound imaging in diagnostics of Monteggia lesion in children - Čepelík, Martin; Hendrych, Jan; Melínová, Hana; Havránek, Petr; Pešl, Tomáš (Journal of children's orthopaedics, 2022)
PURPOSE: The aim of the study is to evaluate the use of ultrasound imaging in diagnostics of Monteggia lesion in children where conventional radiographs and the use of the radiocapitellar line fail to provide an accurate diagnosis. METHODS: Prospective diagnostic study of 70 patients treated between May 2018 and July 2021 in a pediatric level 1 trauma center. In 20 patients with the confirmed radiographic diagnosis of Monteggia lesion, an ultrasound of the humeroradial joint was performed to determine signs of both normal and dislocated elbow joint. In 36 patients with suspected humeroradial dislocation on plain radiographs, ultrasound imaging was performed to determine the definitive diagnosis. Overall, 14 patients with elbow joint injury other than humeroradial dislocation were excluded from the study. RESULTS: The "double-hump sign" and the "congruency sign" were determined as normal findings on ultrasound of the humeroradial joint. These signs were applied to patients with unclear findings on radiographs. In three patients, the dislocation of the humeroradial joint was confirmed by ultrasound. In two patients, "defect in congruency sign" was seen during reduction despite normal radiographs, which required re-reduction. In 31 patients, dislocation of the humeroradial joint was refuted. In 34 out of the 36 patients, the diagnosis determined by ultrasound was confirmed in follow-up. Two patients did not attend the follow-up examination. CONCLUSION: Ultrasound imaging is an accessible, non-invasive, and dynamic point-of-care method that can be applied in children suffering from suspected humeroradial dislocation and/or subluxation. LEVEL OF EVIDENCE: Level III-diagnostic study.
Keywords: elbow; child; Ultrasound; Monteggia; sonography